A novel method for dynamic analysis of complex multi-segment cable systems. (August 2020) - Fei, Han; Zichen, Deng; Danhui, Dan
Highlights: An exact method for dynamic analysis of multi-segment cable systems is proposed. Multiple effects such as flexural stiffness, sag, and elastic supports are considered. The closed-formed frequency equation of the system is derived. An improved Wittrick-Williams algorithm is proposed to solve the transcendental frequency equation. The accuracy of the method is verified by experiment. Abstract: In actual engineering, the cable structure is divided into several natural cable segments due to the existence of lateral supports. During the vibration, each cable segment will have different static and dynamic configurations, which greatly increases the difficulty of structural dynamic analysis. To accurately analyze the dynamic characteristics of this type of systems, this paper proposes an exact dynamic analysis method which can consider the influence of multiple factors such as bending stiffness, sag, and additional cable force based on dynamic stiffness theory, and the analytical expression of the additional cable forces of multi-segment cable systems is obtained. Besides, to consider the geometric nonlinear characteristics of small sag cables, an improved Wittrick-Williams algorithm is proposed, which is suitable for solving the frequency equation of multi-segment cable system. The accuracy of the method is verified by experiment and the finite element method.